PENGARUH SERANGAN KUMBANG AMBROSIA XYLEBORUS SP. TERHADAP KUALITAS KAYU TUSAM (PINUS MERKUSII). - Paimin Sukartana (Jurnal Penelitian Hasil Hutan, 1992)
Some  green   logs of  tusam   (Pinus  merkusii Jungh et de Vr.)  infested by the  ambrosia   beetle  Xyleborus  sp. were  obserbed.  About one thousand  lunnels  per-square  meter  were  shown  on  the  entire  surface of each  log.   The beetle  bored  direclly into  the  logs,   causing wood  damage.The damaged   grades  of sawntimbers  converted  from  the infested  logs showed   varied.   The  most  langential sawtimber  was  highly  affected,  bul by then  the damage decreased  very sharply  toward  the  radial  area  in accordance   with  a regression  equation :      Y = 1840. 70 - 546. 63. lnX       r  = 0.98where          X  = depth  of sawntimber surface  measured  fram  the most  tangential   area  (cm).       Y = number of tunnels per-square  meter.The  infested  area   of  the  wood  was  mostly  in the  peripheral   part  of the  logs.   Of an observed  log,  it  showed   thet  in  average   of 991,.48   lunnels  per-square  meter   appeared   in a 5 cm  thickness   of that part,   and then  231.54    and   9. 73 tunnels  per-square  meter   in the consecuuve   second   and third  5 cm  of the  inner pan. the wood part  of more  than  15  cm  in depth  remained  intack.